2019
DOI: 10.1002/csr.1717
|View full text |Cite
|
Sign up to set email alerts
|

Corporate responsibility and the social risk of new mining technologies

Abstract: Advances in computing, robotics, artificial intelligence, communications, materials, and interactive technologies are disrupting the business-society interface in almost all sectors. The mining industry is projecting an overwhelmingly positive narrative about the new technologies it is investing in and is eager to promote their economic benefits. What is lacking, however, is discussion about how these technologies will be experienced by those most immediately impacted by mining: local communities.Mine-communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Managing ESG&R risks and a framework within which companies can engage with local communities and legitimize their operations is able thanks to CSR programs (cf. Keenan et al, 2019). In the above context Jo and Na (2012) found that the top management of U.S. firms in controversial industries (such as alcohol, tobacco, gambling) is, in general, risk averse and that their CSR engagement helps their risk management efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Managing ESG&R risks and a framework within which companies can engage with local communities and legitimize their operations is able thanks to CSR programs (cf. Keenan et al, 2019). In the above context Jo and Na (2012) found that the top management of U.S. firms in controversial industries (such as alcohol, tobacco, gambling) is, in general, risk averse and that their CSR engagement helps their risk management efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the coordinate of which at 0,325   is max 0, 6946 a  . Thus, it is necessary to consider the motion of the amber particle in the vertical direction, taking into account Archimedes force, vibrations of the working body, as well as the forces of relative resistance of the medium and viscous friction [30][31][32][33][34][35][36]. In this case, given the results already obtained and the assumption that the positive direction of the coordinate axis is directed vertically upwards, the equation of motion of the floating particles can be written as follows:…”
Section: Analysis Of Models Of Motion Of An Amber Particle Under Hydrmentioning
confidence: 99%
“…where μ -the dynamic viscosity of the liquefied medium; δ -diameter of particles of soil skeleton containing amber, m; ρ g -air density, kg/m 3 ; ρ 0 -density of water saturated amber medium, kg/m 3 ; v g -air speed, m/s; v 0 -the sliding velocity of particles of amber-containing medium, m/s. Substituting expression (37) into formula (38), moving from a dynamic coefficient of viscosity to a kinematic coefficient of viscosity, conducting the corresponding transformations and transition to dimensionless quantities, taking into account formula (34), after approximating the dependence of the coefficient of proportionality on the ratio of the density ratio and air by a power function, we obtain the following expression for calculating the magnitude σ:…”
Section: Analysis Of Models Of Motion Of An Amber Particle Under Hydrmentioning
confidence: 99%
“…While the industry has been keen to promote this investment as a cleaner, cheaper, safer and more socially responsible form of production, this 'upside' narrative hides numerous downsides, including the creation of surplus labour. Moreover, there is little indication that the industry has considered how these technology trends will affect local communities (Keenan et al, 2019), particularly in those regions where Indigenous landowners have entered into land use agreements with mining companies in exchange for employment opportunities and other economic benefits (Holcombe & Kemp, 2019). Here, automation extends the source level injustices we have discussed, rather than liberating mine-affected communities.…”
Section: Concluding Remarks: Is It Just a Transition?mentioning
confidence: 99%